Pengaruh Harga, Promosi, Dan Brand Image Terhadap Minat Beli Konsumen Dalam Menggunakan Produk Pada Aplikasi Maxim Di Kota Malang - Malik, Abdul; Djaelani, Abdul Kodir; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to analyze the influence of price, promotion and brand image on consumer buying interest in using products on the Maxim application in Malang. In this research, data collection methods were used using questionnaires. The population of this research is Maxim application users in Malang with a sample of 75 respondents. The analysis technique used is multiple linear regression and hypothesis testing using SPSS for Windows software. The conclusions of this research are price promotion and brand image simultan have a positive and significant effect on consumer buying interestm,  price simultan has a positive and significant effect on consumer buying interes, promotion simultan has a positive and significant effect on consumer buying interest,  brand Image simultan has a positive and significant effect on purchasing interest.  Keywords: Price, Promotion, Brand Image, and Purchase Interest